Предмет: Алгебра,
автор: suffleter
Упростите выражения:
1) (х – 2)(х – 11) – 2х(4 – 3х)
2) (а + 6)(а – 3) + (а – 4)(а + 5)
Ответы
Автор ответа:
0
1)(х – 2)(х – 11) – 2х(4 – 3х) = x²-11x+2x+22-8x+6x²=7x²-17+22
2)(а + 6)(а – 3) + (а – 4)(а + 5) = a²-3a+6a-18+a²+5a-4a-20=2a²+4a-38
2)(а + 6)(а – 3) + (а – 4)(а + 5) = a²-3a+6a-18+a²+5a-4a-20=2a²+4a-38
Похожие вопросы
Предмет: Информатика,
автор: veronika22233
Предмет: Геометрия,
автор: hasteboom1
Предмет: Немецкий язык,
автор: Gold2905
Предмет: Литература,
автор: a230104
Предмет: Математика,
автор: liysiataganrog